Comparative advantage of rice production in Bangladesh: A long-term quasi-response assessment for aman (wet) season - Islam, Mohammad Ariful; Sarkar, Md Abdur Rouf; Rahman, Mohammad Chhiddikur; Rahaman, Md Shajedur (Fundamental and Applied Agriculture, 2021)
This study aims to investigate whether Bangladesh has a comparative advantage in producing rice in the long run in the Aman (wet) season. With that view, we estimated ‘Domestic Resource Cost (DRC)’ as an indicator of comparative advantage using the time series data from 2010-11 to 2020-21. The study also captured paddy yield, border rice price, marketing spread between the wholesale and retail level, and different inputs price changes using sensitivity analysis. Data were obtained from the database on the food situation, published by the Food Planning and Monitoring Unit (FPMU), Ministry of Food, Peoples’ Republic of Bangladesh. The analyses show that Bangladesh has a comparative advantage in modern variety (MV) rice production in the Aman season at import substitution. DRC values for Aman (wet) season are <1 in all the periods (2010-11 to 2020-21) except 2017-18 and 2018-19. The sensitivity analysis shows that all the indicators like paddy yield, marketing spread between the wholesale and retail level, border price of rice, urea, triple super phosphate (TSP), and muriate of potash (MoP) pertinent to this particular analysis strongly inﬂuence (both increased and decreased) the DRC values. When the paddy yield, border price of rice, border price of rice, urea, TSP, and MoP inputs prices have increased gradually and non-tradable inputs, marketing spread between the wholesale and retail level price and border price of urea, TSP, and MoP inputs price have decreased progressively, all the DRC values have decreased gradually and vice versa. So, the level of comparative advantage of Aman (wet) season rice production has been increased chronologically at import substitution and vice versa. To achieve a long-run comparative advantage, government, as well as policymakers, should focus on reducing price spread between the wholesale to retail levels, the border price of rice at the farm gate level, and the border prices of rice, urea, TSP, and MoP of farm gate level. Research efforts need to prioritize developing new varieties with higher yield potentiality and proper management packages for the Aman (wet) season.